New Japanese Regulatory Frameworks for Clinical Research and Marketing Authorization of Gene Therapy and Cellular Therapy Products - Nagai, Sumimasa; Ozawa, Keiya (Current Gene Therapy, 2017)
Introduction: In Japan, the Pharmaceuticals and Medical Devices Law was passed in 2014. In this new law, regenerative medical products were defined, and a conditional and term-limited approval system only for regenerative medical products was instituted. Therefore, regenerative medical products can be approved based on phase I and/or II trials. Gene therapy and adoptive cellular therapy are categorized as regenerative medical products. This law is intended for registration trials for marketing authorization. The Act on the Safety of Regenerative Medicine was also implemented in 2014. This act is intended for clinical research and medical practice involving processed cells other than registration trials. Under this act, a review of plans on medical treatments or clinical studies by a certified committee and submission of the plans to the Ministry of Health, Labour and Welfare (MHLW) are mandatory. The MHLW instituted the SAKIGAKE (meaning a pioneer or forerunner in Japanese) designation system in 2015. This designation is similar to the breakthrough therapy designation in the US and PRIME in the EU. In addition, the MHLW started the “Project for Enhanced Practical Application of Innovative Drugs, Medical Devices and Regenerative Medical Products” to promote personnel exchange and cooperation in writing of guidelines on the evaluation of innovative medical products between the Pharmaceuticals and Medical Devices Agency and academia. Some new guidelines regarding gene and cellular therapy were published. Conclusion: In this review, we comprehensively described these complicated regulations and problems to be solved in order to facilitate global readers’ understanding of Japanese regulatory frameworks.
Keywords: PMDA